PERBANDINGAN KEMAMPUAN EKSTRAK KULIT PISANG AGUNG SEMERU DAN PISANG MAS KIRANA VARIETAS LUMAJANG DALAM MENGHAMBAT PERTUMBUHAN Candida albicans - Dwi Nur Rikhmasari (Florea : Jurnal Biologi dan Pembelajarannya, 2017)
Agung Semeru banana and Mas Kirana, is one of the typical banana varieties found in Lumajang Regency. Where on the banana peel extraction contain various antifungi compounds. The purpose of this research is to know the difference of banana extract of Agung Semeru and banana Mas Kirana varieties of lumajang, in inhibiting the growth of pathogenic fungi Candida albicans, and to know the optimal concentration which can inhibit the growth of Candida albicans. The method used was Completely Random Design (RAL) with four of factors, that is: 0, 25, 50, 75 and 100 %. The results were analyzed with Anova test and Duncan test multiple ranger test at the level of 5%. Each treatment was repeated three times. The results show that there is an effect of giving extract of Semeru banana peel (sig = 0,00) and banana Mas Kirana (sig = 0,00) to Candida albicans growth at various concentration (0%, 25%, 50%, 75% and 100%). For extract of Semeru banana peel at concentration 75% (3,19  ± 0,84 mm) showed better result from other concentration, while for banana Mas Kirana Lumajang peel extract, at concentration 50% (2,44 ± 0,0 mm) showed better result than treatment other. Ability of antifungal activity of Agung Semeru banana peel extract better than banana Mas Kirana.